2019
DOI: 10.1590/1807-1929/agriambi.v23n1p40-46
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient accumulation in Eucalyptus bark at different population densities

Abstract: The objective of this study was to quantify the accumulation of nutrients in the bark of four eucalyptus clones at 12 years-of-age, planted at different population densities, and the values were extrapolated to kg of nutrients per hectare. The experiment used randomized blocks in a 4 × 3 factorial design and three replications, with four Eucalyptus clones (2486, I182, I144, and GG100) planted at three population densities (416, 833, and 1111 trees ha-1). The rigorous cubage of three trees per plot was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Rocha et al (2018) evaluated the effect of different plant spacings on bark thickness and properties in Eucalyptus grandis × E. camaldulensis and reported that plant spacing positively affects bark properties. Martins et al (2019) have quantified the macronutrients of 12-year-old Eucalyptus bark planted at three planting densities, concluding that higher plant density contributed to higher bark production and greater nutrient accumulation per area.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al (2018) evaluated the effect of different plant spacings on bark thickness and properties in Eucalyptus grandis × E. camaldulensis and reported that plant spacing positively affects bark properties. Martins et al (2019) have quantified the macronutrients of 12-year-old Eucalyptus bark planted at three planting densities, concluding that higher plant density contributed to higher bark production and greater nutrient accumulation per area.…”
Section: Introductionmentioning
confidence: 99%
“…Despite representing 8% of tree biomass and containing significant amount of nutrients, such as N, P and K (Martins et al . 2019), only 7% of tree bark returns to ecosystem via natural soil fertilizer, and less than 1% is reused as raw material for other agricultural purposes (IBÁ 2020). The same occurs for spent mushroom compound that is also rich in N, P and K (Meng et al .…”
Section: Resultsmentioning
confidence: 99%
“…Diferentemente disso, para Martins et al (2019), o menor espaçamento entre plantas resultou no aumento da competição intraespecífica entre clones de eucalipto, com menor acumulação nutricional e alterações na partição da biomassa. No entanto, evidências mostraram que dependendo do clone, a produção de biomassa, especialmente de casca, é diferenciada em densidades maiores, com menor acúmulo nutricional, indicando maior eficiência nutricional.…”
Section: Discussionunclassified